Penerapan Prinsip Jurnalistik Bill Kovach Pada Media Komunitas - Putri, Devy Indriyana; Suherdiana, Dadan; Darsono, Dono (Jurusan Ilmu Komunikasi, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2022)
ABSTRACTCommunication media began to develop after the reform era, to be precise in 1998. Community media is a type of media, both print and electronic, that is present in certain communities or communities. The main character of community media is that it has a limited (local) reach. UrbanCikarang is one of the largest community media outlets in Bekasi District, which has been established for six years and has become an information forum for Bekasi District residents who can provide various information from news about government and other information that is happening in Bekasi District. UrbanCikarang is one of the community media that represents Bekasi Regency in several community media competitions at both the regional and national levels and has received several awards, one of which being the best ICT community at the West Java Province level in 2015.Keywords: UrbanCikarang, Journalism, Community MediaÂ